Penilaian Keaslian Bangunan Candra Naya Jakarta Konservasi Menggunakan Instrumen Nara Grid - Farah Athaya Salsabilani; Yusfan Adeputera Yusran; Joko Triwinarto Santoso (CV. Gio Architect, 2023)
Candra Naya is a Chinese style heritage building that has been standing since the 19th century. During its journey, this building has undergone several conversions from being a residence to now becoming a museum. After being conserved adaptively into a museum and new buildings construction arose around it, many adjustments to the Candra Naya building were made. This study was conducted to assess the authenticity of the post-conservation of Candra Naya using the Nara Grid instrument. This research using an exploratory mixed method, a combination of qualitative and quantitative study. The results of both research methods were analyzed into six aspects and four dimensions of the Nara Grid. The evaluation results indicate that the authenticity of the Candra Naya building is in the proper category. The building elements, in visually, spatially, and structurally terms, are still following the original, where some materials are only polished for maintenance. Some of the changes made are non-destructive and only as an adjustment to the new building built around the site.